Răspunsuri

2014-09-20T23:11:43+03:00
A) 2x + 24 - 6x + 3 = 5x + 9
2x - 6x - 5x = - 24 - 3 + 9
- 9x = - 18
x = 18 : 9
x = 2
b) 4x + 1 - 3x - 6 = 2x - 8
4x - 3x - 2x = - 8 - 21 + 6
- x = - 23
x = 23
c) 2x + 6 - 10 + 2x = 7x + 2
2x + 2x - 7x = - 6 + 10 + 2
- 3x = 6
x = - 6 : 3
x = - 2
d) 6x + 11 - 5x + 10 = 4x - 12
6x - 5x - 4x =  -11 - 10 - 12
- 3x = - 33
x = 33 : 3
x = 3

 
2014-09-20T23:55:14+03:00
A) 2x+24-6x+3=5x+9
24-9+3=5x+6x-2x
18=9x
x=2
d) 6x+11-5x+10=4x-3
11+3+10=4x+5x-6x
18=3x
x=6
c) 2x+6-10+2x=7x+2
6-10-2=7x-2x-2x
-6=3x
x=-2
b) 4x+1-3x-6=2x-8
4x-3x-2x=-8-1+6
-x=-3
x=3